Current trends and therapies in orchialgia management. (June 2021) - Campbell, Kevin; Lipshultz, Larry
The management of pain is a complex condition that will be encountered by most practicing clinicians. In the genitourinary community, testicular pain may be classified as acute or chronic. Initial evaluation of chronic groin and scrotal content pain (CGSCP) begins with a detailed history and physical examination to elucidate the presenting pathology. Multiple therapy algorithms have been proposed with no definitive consensus; however, most begin with conservative intervention and medical management prior to advancing to more invasive procedures. Surgical approaches may range from reconstruction, as in vasovasostomy for post-vasectomy pain syndrome, to excision of the offending agent, as in epididymectomy. This review seeks to focus on chronic pain in the genitourinary community and review techniques of pain management in the current intervention for orchialgia, as well as identify future methods of treatment.